MENINGKATKAN MOTIVASI BELAJAR PADA PELAJARAN BAHASA ARAB DENGAN METODE PEMBELAJARAN ROLE PLAYING - Salsabila, Alfiana (Pengelola Jurnal Politeknik Negeri Ketapang, 2025)
Arabic language learning in schools often faces the problem of low student learning motivation. This condition is caused by the perception that Arabic is a difficult subject, as well as the use of conventional teaching methods that lack variation and student involvement. Low learning motivation has an impact on students’ lack of activeness, interest, and confidence in using Arabic orally. Therefore, it is necessary to implement a learning method that can effectively improve students’ learning motivation. This study aims to increase students’ learning motivation in Arabic language learning through the implementation of the role playing learning method. This research employed a classroom action research (CAR) approach conducted in two cycles. The research subjects were students at the secondary education level who participated in Arabic language learning. Data were collected through observation, learning motivation questionnaires, and documentation. The collected data were analyzed using descriptive quantitative analysis to identify changes in students’ learning motivation at each stage of the research. The results of the study indicate that the implementation of the role playing learning method significantly improved students’ learning motivation. In the pre-action stage, students’ learning motivation was categorized as low. After the application of the role playing method in the first cycle, students’ learning motivation increased to a moderate level, and in the second cycle, it reached a high level. The improvement in learning motivation was reflected in students’ increased activeness, enthusiasm, and confidence in using Arabic during the learning process. Based on these findings, it can be concluded that the role playing learning method is effective in improving students’ learning motivation in Arabic language learning and can be used as an innovative and interactive alternative teaching strategy.